Analisis Risiko Pembiayaan Syariah Pada Sektor Pertanian - Khonsa Tsabita (Department of Islamic Economics, IPB University, 2014)
One of the main problems of agricultural sector in Indonesia is the lack of financial support. There are many financing programs which available to overcome this problem, but this problem still persist. Thus, the alternative financing scheme such as Islamic financing that concern on risk sharing concept rather than profit, is a feasible solution. Moreover, the increase of Islamic financing on agricultural sector requires many studies. One of them is about financing risk analysis as well as risk management instruments and systems. This research is applied at BPRS (Islamic Rural Bank) Amanah Ummah, Leuwiliang, Bogor, Indonesia, which provides financing for agricultural business. Thus, this research is focused on analyzing Islamic financing risk and measuring potential loss. In addition, this Islamic financing risk is analyzed with Enterprise Risk Management (ERM) framework method and the potential loss is measured with creditrisk+ method. Overall, this research contributes to literatures on Islamic financing in agricultural sector and provides ground-study related to financing risk analysis on Islamic microfinance institutions.